PENGARUH PENGGUNAAN CDI RACING DAN JENIS BAHAN BAKAR TERHADAP DAYA, TORSI, DAN KONSUMSI BAHAN BAKAR PADA SEPEDA MOTOR HONDA VARIO 110CC TAHUN 2010 - Irfanda Adi; Ranto Ranto; Husin Bugis (Nozel : Jurnal Pendididikan Teknik Mesin, 2020)
This research is aimed to invesitage : (1) the possibility effect of CDI racing use to power, torque, and fuel consumption for 110CC of Honda Vario motorcycle produced in 2010, (2) the possibility use of fuel to power, torque, and fuels consumption for 110CC Honda Vario motorcycle produced in 2010, and (3) the possibility effect of CDI racing use and kind of fuels to power, torque, and fuel consumption for Honda Vario 110CC motorcycle produced in 2010. The method used in this research was experimental, by applying descriptive data analysis.Honda Vario110CC motorcycle produced in 2010 was as a sample of this research. The independent variables in this research are CDI racing, CDI standard, RON 88 premium, RON 90 pertalite, and RON 92 pertamax. The dependent variables are power, torque, and fuel consumption. The findings indicate: (1) There is an effect of CDI racing use to Honda Vario110CC motorcycle produced in 2010. The use of CDI racing is able to increase the power to 0,16 HP or 2%, and the torque to 0,01 N.m or 0,08%, it decreses the fuel consumption to 16 ml/km or 22 ,86%, (2) There is an effect of fuel use to Honda Vario 110CC motorcycle produced in 2010. The fuel use of RON 92 pertamax to this kind of motorcycle is able to increase the power to 0,06HP or 0,75% and the torque to 0,2 N.m or 1,74%, it reduces the fuel of consumption to 4 ml/km or 10,71%, (3) There is an effect of CDI racing use and kind of fuels to Honda Vario110CC motorcycle produced in 2010. The use of CDI racing and RON 92 pertamax for this kind of motorcycle is able to increase the power to 8,33 HP andthe torque to 11,70 N.m, with the reduction of fuel consumption to 17,33 ml/km.